Encyclopaedia of Historical Metrology, Weights, and Measures Volume 3 - Gyllenbok, Jan (Science Networks. Historical Studies,, 2018)
This third volume of Gyllenbok's encyclopaedia of historical metrology comprises the second part of the compendium of measurement systems and currencies of all sovereign states of the modern World (J-Z). Units of measurement are of vital importance in every civilization through history. Since the early ages, man has through necessity devised various measures to assist him in everyday life. They have enabled and continue to enable us to trade in commonly and equitably understood amounts, and to investigate, understand, and control the chemical, physical, and biological processes of the natural world. The encyclopeadia will be of use not only to historians of science and technology, but also to economic and social historians and should be in every major academic and national library as standard reference work on the topic.